PERAN BUDAYA ORGANISASI DALAM MENINGKATKAN EFEKTIVITAS DAN PRODUKTIVITAS ORGANISASI - Melly Zahrani; Nabila; Nadhifa Ahmanil Zahra; Naswa Paisa; Nessa Alfitri; Nuri Wulandari; Ferdino Wedi Sanjaya (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Organizational culture is a key factor influencing an organization’s success in achieving its established goals. Organizational culture is reflected through a set of values, norms, beliefs, and habits that serve as guidelines for organizational members in how they think, behave, and act. Fostering a positive organizational culture can create a harmonious work environment, increase member engagement, and strengthen commitment to achieving organizational goals. This article aims to examine the role of organizational culture in enhancing organizational effectiveness and productivity through an analysis of relevant literature. The method used is a literature review (library research) that examines various theories, concepts, and previous research findings related to organizational culture, organizational effectiveness, and work productivity. The results of the study indicate that a strong organizational culture can foster positive work behavior and enhance motivation, discipline, responsibility, and cooperation among organizational members. In addition, organizational culture also contributes to creating more open and effective communication, reducing potential conflicts, and fostering innovation and creativity in the performance of duties. These conditions have a positive impact on the organization’s effectiveness in optimally achieving its goals. In terms of productivity, organizational culture plays a role in improving both the quality and quantity of work output, optimizing the use of available resources, and driving improvements in individual and overall organizational performance. Thus, organizational culture is not only a distinctive characteristic that sets one organization apart from others but also serves as a strategic factor that supports increased organizational effectiveness and productivity in the face of an ever-evolving environment and its challenges.